Robotic‐assisted balloon angioplasty and stent placement with distal embolic protection device for severe carotid artery stenosis in a high‐risk surgical patient. Issue 2 (5th May 2020) - George, Jon C.; Tabaza, Luai; Janzer, Sean
Abstract: The use of robotic assistance in endovascular interventions may facilitate smoother procedures with fewer device manipulations, improve precision and accuracy of device deployment, and reduce exposure to fluoroscopic radiation. We used the CorPath GRX Robotic System for carotid balloon angioplasty and stent placement in a patient with limited surgical options.